Dynamic Stereotype and Communicative Competence in Foreign Language Learning - Aryna Frumkina (Pedagogical Discourse, 2025)
The article reveals the psychophysiological nature of the dynamic stereotype and its role in the development of foreign language communicative competence. The mechanism of speech automatization in the process of language acquisition is analyzed, with emphasis on the consolidation of lexical and grammatical units in memory. The study highlights the importance of functional and contextual repetition as key factors in the formation of speech automatisms. Special attention is paid to the conditions that ensure effective reinforcement of linguistic material, including the frequency, variety, and communicative relevance of speech practice. The paper presents empirical research results confirming a strong correlation between repetition quality and the level of dynamic stereotype formation among language learners. The findings suggest that a communicatively oriented approach, grounded in psycholinguistic principles, significantly enhances the stability and fluency of foreign language use. The dynamic stereotype is interpreted not only as a product of habitual practice but as a target outcome of purposeful language training that fosters automaticity and confidence in spontaneous communication.